Design Currency : Understand, define, and promote the value of your design work - O'Grady, Jenn; O'Grady, Ken (New Riders, 2013)
The world needs beautiful design. But aesthetics are inherently subjective. In Design Currency, authors Jenn and Ken Visocky O'Grady show you how to frame the value of your design work in terms that your business partners will both understand and respect. An actionable resource, Design Currency empowers you to do your job with less pushback on aesthetic decisions, encourages earlier involvement in the creation process, and makes it easier for you to justify your fees. For a designer, understanding how your work creates value is essential to growing your business and building better, more profitable relationships. Those relationships are easier to initiate, establish, and retain when you can clearly explain how your capabilities meet your client's needs. This book shows you how to do exactly that. In Design Currency, you will learn how to: Leverage traditional design skills in new ways Measure the value that your design work brings to a project Articulate that value so that you can position yourself as a partner in the development process Charge what you're worth and prevent your job from getting crowd-sourced or out-sourced Generate business value by better identifying audience needs